2020
DOI: 10.15174/au.2020.2123
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationship and condition factor of Centropomus viridis (Actinopterygii: Perciforms: Centropomidae) in the north coast of Nayarit

Abstract: This study poses two objectives: to determine whether the growth of females and males of the C. viridis is isometric, and whether the commercial fishing changes the condition of snook. The information regarding the length-weight relationship (LWR) is basic for the development of management strategies and conservation of the white snook. The length-weight relationship condition analysis is presented for the snook C. viridis fishery in the north coast of Nayarit. A non-experimental, longitudinal aleatory study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…The condition-factor analysis of the three snook species studied in the present work presented a value of K < 1. This result differs from that reported by Tapia Varela et al [47], who showed results for C. viridis indicating a value of K ≥ 1 in males, while the females presented a condition lower than 1 (0.98 < 1). Our results may indicate that fishing efforts could be generating variations in the fishing conditions of the populations of the three species in the study areas.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The condition-factor analysis of the three snook species studied in the present work presented a value of K < 1. This result differs from that reported by Tapia Varela et al [47], who showed results for C. viridis indicating a value of K ≥ 1 in males, while the females presented a condition lower than 1 (0.98 < 1). Our results may indicate that fishing efforts could be generating variations in the fishing conditions of the populations of the three species in the study areas.…”
Section: Discussioncontrasting
confidence: 99%
“…The negative allometric growth for C. viridis reported in the present study is similar to that estimated by Tapia Varela et al [47] on the north coast of Nayarit (in the general analysis of length and weight for males and females, b = 2.958 was reported). However, Labastida-che et al reported isometric growth for both sexes of white snook in the lagoon systems of the state of Chiapas (b = 2.99) [48].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation